3/2x-13=5x+1

Simple and best practice solution for 3/2x-13=5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/2x-13=5x+1 equation:



3/2x-13=5x+1
We move all terms to the left:
3/2x-13-(5x+1)=0
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
We get rid of parentheses
3/2x-5x-1-13=0
We multiply all the terms by the denominator
-5x*2x-1*2x-13*2x+3=0
Wy multiply elements
-10x^2-2x-26x+3=0
We add all the numbers together, and all the variables
-10x^2-28x+3=0
a = -10; b = -28; c = +3;
Δ = b2-4ac
Δ = -282-4·(-10)·3
Δ = 904
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{904}=\sqrt{4*226}=\sqrt{4}*\sqrt{226}=2\sqrt{226}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-28)-2\sqrt{226}}{2*-10}=\frac{28-2\sqrt{226}}{-20} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-28)+2\sqrt{226}}{2*-10}=\frac{28+2\sqrt{226}}{-20} $

See similar equations:

| (x+3)^2-1=35 | | -12k–-3k–14k+20k=-6 | | 10(4)^2x-1-5=7 | | 2(96+2w)=80-3w | | 8p–6p=12 | | (x+3)^2​−1=35 | | x+1,5=6 | | 43h+2=17+5 | | x-9=3x+-7 | | 1/4n=60 | | 5n-3=38 | | x+8=3x-3 | | -3h=-5-(1/2) | | c17=3 | | 12=5y+6 | | 7x+6(-3x+3)=-48 | | -2(3n-5)+5n=(6(n-3) | | -5b+14=-4b-9 | | 3(2z+1)=6z-2)+14 | | 3j=4/5 | | 12z-9z+-z-8z-10z=16 | | 23=5(x+5)-7x | | −2/3x+37=12 | | 5x+5=1x+9 | | 12z–9z+-z–8z–10z=16 | | 7x/2=20 | | 6x=x^2-4x+11 | | 5z-z-3z=3 | | 7(w+2)-1=6w+14 | | x+5/x-4+x-9/5x-4=1 | | 4m+m=20 | | 6((3r-5))/2+4=52 |

Equations solver categories